RESISTANCE TO ACETYLSALICYLIC ACID AND PREVALENCE OF THROMBOSIS IN PATIENTS WITH STABLE ANGINA - N. F. Putchinyan; N. V. Furman; P. Ya. Dovgalevskyi (Рациональная фармакотерапия в кардиологии)
Aim. To estimate the prevalence of atherothrombotic complications depending on platelet sensitivity to acetylsalicylic acids (ASA) in patients with stable angina.Material and methods. 96 patients with stable angina of II-III functional classes received basic therapy included ASA (125 mg daily) to prevent atherothrombotic complications. Platelet ability to aggregation was assessed with laser aggregometer. Resistance to ASA was determined, if cumulative index of platelet aggregation (after stimulation with ADF, 5 µmolł) remain on the level of 50-70% in spite of ASA. Atherothrombotic complications (cardiovascular death, myocardial infarction, unstable angina, cerebral stroke) were registered during 24-36 months.Results. Resistance to ASA was detected in 24% of patients. Atherothrombotic complications were registered in 66% of patients with ASA resistance (myocardial infarction or unstable angina were observed in 14 patients of 21 ones) and in 27% of patients with sensitivity to ASA (myocardial infarction or unstable angina were observed in 19 of 70 ones). Besides, resistance to ASA was associated with high rate of thrombosis of installed stents or coronary artery bypasses.Conclusion. In patients with unstable angina insufficient inhibition of platelet aggregation with ASA is associated with 2, 45 times increase in risk of atherothrombotic complications and higher rate of thrombosis of installed stents or coronary artery bypasses.